Pengenalan Keselamatan Dan Kesehatan Kerja Di PT Cita Rasa Palembang - Utami Wahyuningsih; Eko Sulistyo; Halim Rusjdi; Win Alfalah; Sudirmanto Sudirmanto; Eri Prabowo (Terang, 2021)
Occupational Safety and Health now occupies an important place in the company, especially in industrial work. A sense of security and comfort at work is a demand for companies to be able to fulfill it in order to provide job security for workers. This study aims to evaluate the implementation of K3 in the implementation of work in the small industry of Pempek Belida in PT Cita Rasa Palembang based on SMK3. The study used survey questionnaires and direct interviews in the field, followed by identification of industrial locations, visual surveys in the industry and documentation taking in the field. At PT Cita Rasa Palembang, the implementation of Occupational Safety and Health (K3) has been going quite well, because in this Industry the work organizers have provided personal protective equipment (PPE) for workers and the socialization of K3 has also been carried out by the owners and workers quite understand it but there are still impressive workers who do not care about the Occupational Safety and Health, it can be seen from the results of the questionnaire stated, 100% (Yes) because the work of the food industry has provided personal protective equipment (PPE); 98% know what is meant by Occupational Safety and Health; and 100% of workers claim there is a guarantee of Occupational Safety and Health.